Pengaruh Komunikasi Organisasi, Komitmen Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior di Bagian Umum Kantor Sekretariat Daerah Kabupaten Kebumen - Siti Nur Azizah; Elly Prasetiyowati (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
This study aimed to determine the effect of communication, organizational commitment and job satisfaction on employee organizational citizenship behavior common part of the District Secretariat Kebumen. The research sample is a population that is saturated sample survey method. Data were taken using a questionnaire and to test the validity, reliability and assumptions of classical and rock data is regressed with SPSS. T test results showed each variable communication, organizational commitment and job satisfaction have a significant effect on OCB. While the F-test shows that the three independent variables jointly significant effect on OCB in the Division of General Office of the Secretariat of Kebumen. Variable organizational communication, organizational commitment and job satisfaction can be used to improve the OCB employee at the Office of the General Secretariat Kebumen district.